Perencanaan Strategi Pengembangan Usaha Menggunakan Formulasi Matrik SWOT dan Metode QSPM - Laura Prasasti; Ayu Feranika (Journal of Trends Economics and Accounting Research, 2024)
This study aims to formulate appropriate marketing strategy planning alternatives through analyzing the approach of internal factors and external factors as an effort to face competitors from Aulia Jambi Toothpick Chips. The sampling method in this study was purposive sampling, so that the total sample obtained was 30 respondents consisting of 5 from internal, namely the management of the Aulia Toothpick Chips factory employees and 25 from external, namely consumers. The analysis method used in this research is SWOT analysis (Strength, Weakness, Opportunities, and Threats) through an internal and external factor approach with the calculation of the IFE and EFE matrix table analysis and the QSPM method. The results of IFE internal factors and EFE external factors, obtained a Strength value of 2.08 and Weaknesess of 1.08 while the Opportunities value is 1.92 and Threats is 1.38. Based on the results of the calculation of the analysis quadrant diagram using the IFE and EFE approaches, it can be concluded that the x, y axes are at the Quadrant I point, so the strategy that must be applied in this condition is to support aggressive growth policies (Growth Oriented Strategy). So that the right alternative strategy for Aulia's Toothpick Chips MSME players is the S-O (Strength-Opportunities) strategy. The S-O (Strength-Opportunities) strategy, which is referred to as an aggressive growth strategy, is through the use of digital marketing for the marketing system, providing special offers and maintaining product quality.